Yi-Shen-Hua-Shi granules inhibit diabetic nephropathy by ameliorating podocyte injury induced by macrophage-derived exosomes - Mingzhu Liang; Mingzhu Liang; Xiaodong Zhu; Di Zhang; Wenfang He; Jinshi Zhang; Shizhu Yuan; Qiang He; Juan Jin (Frontiers Media S.A., 2022)
Objective: To observe the therapeutic effect of Yi-Shen-Hua-Shi (YSHS) granule in podocyte damage and diabetic nephropathy (DN) proteinuria and to explore the corresponding mechanism.Methods: The db/db mice were used to establish the DN model. Serum creatinine (SCr), blood urea nitrogen (BUN), and 24 h urinary proteinuria were detected with specific kits. Glomerular structural lesions and podocyte apoptosis were detected through HE staining, TUNEL assay, and immunofluorescence. The medicated serum of YSHS granule (YSHS-serum) or control serum was prepared. Macrophage-derived exosomes were extracted using an exosome extraction kit. Morphology and the protein concentration of exosomes were evaluated by a transmission electron microscope (TEM) and BCA kit. The activity and apoptosis of podocyte MPC5 cells, the M1 macrophage polarization, and the protein expression of an exosome marker and cleaved caspase were detected by the CCK8 experiment, flow cytometry, and Western blot, respectively. The miR-21a-5p expression in podocytes and the exosomes from macrophages were measured by qRT-PCR. The effect of YSHS granule on the infiltration of M1 macrophages in the kidney tissue in db/db mice was measured by immunofluorescence.Results: The YSHS granule could improve renal function, reduce proteinuria, and inhibit glomerular structural lesions and podocyte apoptosis in db/db mice. High-glucose (HG) stimulation and YSHS granule treatment did not affect the protein concentration in macrophage-derived exosomes. Macrophage-derived exosomes could inhibit the cell viability and increase apoptosis of podocytes, especially the exosomes from macrophages treated with HG and control serum. Compared with the exosomes secreted by macrophages after an HG treatment, the exosome from macrophages treated with HG and YSHS granule showed lower inhibitory effects on podocyte activity, accompanied by the decreased upregulating effects of macrophage-derived exosomes on the miR-21a-5p in podocytes. miR-21a-5p mimics could reduce podocyte activity and promote caspase-3 shearing. M1 polarization of macrophages could change the content of miR-21a-5p in macrophage-derived exosomes. In addition, YSHS granule could inhibit HG-induced M1 polarization of macrophages and M1 macrophage infiltration in renal tissues.Conclusion: The YSHS granule could improve the podocyte injury induced by macrophage-derived exosomes and alleviate the progression of DN. This regulation might be related to the inhibition of M1 macrophage polarization by YSHS granule and the reduction of the miR-21a-5p content in macrophage-derived exosomes.